MYBPC3-associated cardiomyopathy: features of the course and prospects for specific therapy - D. A. Nefedova; R. P. Myasnikov; O. V. Kulikova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2025)
Genetic cardiomyopathies (CMP) are a group of diseases characterized by myocardial pathology not caused by hypertension, coronary artery disease, congenital and acquired defects. Development of imaging methods and molecular genetic diagnostics showed that the traditional phenotypic classification does not fully meet modern needs due to the presence of clinical, morphological and genotypic "crossing" of CMP. At the same time, in recent years, data have been obtained showing that the genetic substrate has a significantly higher prognostic value compared to the phenotype and plays a significant role in risk stratification and the choice of patient management tactics, as well as in family screening. Taken together, this has led to a shift in focus from phenotypic features to genotype as the basis for modern classifications of cardiomyopathy. One example of such a genotype-specific approach is the identification of cardiomyopathy associated with MYBPC3 gene variants as an independent entity. The aim of the article was to describe the role of MYBPC3 gene and the cardiac myosin-binding protein C encoded by it in cardiomyocyte function, to present current literature data on pathogenesis, clinical features and developing strategies for MYBPC3cardiomyopathy treatment, as well as to highlight current problems and directions for future research in this area.